Effects of Promoting-Academics on public and private university students: Promoting-Academics: effects of a Behavior-Analytic Therapy program (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Searching for evidences in behavior-analytic therapy (BAT) is important and urgent. There are a high demand on the university scope in relation to academic or interpersonal difficulties, as well as psychological problems, there also are a lack of studies with a experimental control. This study describes effects of an intervention in BAT, named Promoting-Academics, in a single-subject design of multiple baseline. Five students participated of that, and the program is semi-structured 11-week program was applied by a trained female psychologist, being adjusted and adapted according to the participants’ demands, and it expects case formulation and individual objectives which are object of intervention. In general, results indicated greater behavioral acquisitions and decrease of indicatiors concerning mental health problems after the interventions, with maintenance upon six months. The conclusion is the Promoting-Academics fulfilled its purposes and has applicability to prevention and intervention.
Keywords: Clinical Behavior Analysis; college students; mental health; social skills; evidence-based practice